Comparative differences in the atherosclerotic disease burden between the epicardial coronary arteries: quantitative plaque analysis on coronary computed tomography angiography. (20th November 2020) - Bax, A Maxim; van Rosendael, Alexander R; Ma, Xiaoyue; van den Hoogen, Inge J; Gianni, Umberto; Tantawy, Sara W; Hollenberg, Emma J; Andreini, Daniele; Al-Mallah, Mouaz H; Budoff, Matthew J; Cademartiri, Filippo; Chinnaiyan, Kavitha; et al.
Graphical Abstract: Abstract: Aims: Anatomic series commonly report the extent and severity of coronary artery disease (CAD), regardless of location. The aim of this study was to evaluate differences in atherosclerotic plaque burden and composition across the major epicardial coronary arteries. Methods and results: A total of 1271 patients (age 60 ± 9 years; 57% men) with suspected CAD prospectively underwent coronary computed tomography angiography (CCTA). Atherosclerotic plaque volume was quantified with categorization by composition (necrotic core, fibrofatty, fibrous, and calcified) based on Hounsfield Unit density. Per-vessel measures were compared using generalized estimating equation models. On CCTA, total plaque volume was lowest in the LCx (10.0 ± 29.4 mm 3 ), followed by the RCA (32.8 ± 82.7 mm 3 ; P < 0.001), and LAD (58.6 ± 83.3 mm 3 ; P < 0.001), even when correcting for vessel length or volume. The prevalence of ≥2 high-risk plaque features, such as positive remodelling or spotty calcification, occurred less in the LCx (3.8%) when compared with the LAD (21.4%) or RCA (10.9%, P < 0.001). In the LCx, the most stenotic lesion was categorized as largely calcified more often than in the RCA and LAD (55.3% vs. 39.4% vs. 32.7%; P < 0.001). Median diameter stenosis was also lowest in the LCx (16.2%) and highest in the LAD (21.3%; P < 0.001) and located more distal along the LCx when compared with the RCA and LAD ( P < 0.001). Conclusion: Atherosclerotic plaque, irrespective of vessel volume, varied across the epicardial coronary arteries; with a significantly lower burden and different compositions in the LCx when compared with the LAD and RCA. These volumetric and compositional findings support a diverse milieu for atherosclerotic plaque development and may contribute to a varied acute coronary risk between the major epicardial coronary arteries.